Catalytic activity of various platinum loading in acid electrolyte at 303 K. (October 2017) - Chaiburi, Chakkrapong; Hacker, Viktor
Abstract: The aim of this work is to determine the optimum platinum (Pt) loading on the surface of glassy carbon. By measuring four different Pt loading electrocatalysts, the electrochemical surface area (ECSA), the mass activity (MA), the roughness factor (rf ) and the kinetic current (ik ) was observed. The specific activity (SA) increased for decreasing Pt loading. At high Pt loadings, aggregation of Pt in the active layer was observed.